Atomically Precise Noble Metal Clusters Harvest Visible Light to Produce Energy. Issue 4 (3rd February 2017) - Jeseentharani, V.; Pugazhenthiran, N.; Mathew, Ammu; Chakraborty, Indranath; Baksi, Ananya; Ghosh, Jyotirmoy; Jash, Madhuri; Anjusree, G. S.; Deepak, T. G.; Nair, A. Sreekumaran; Pradeep, T.
Abstract: Atomically precise gold and silver clusters are a new class of sensitizers which can be used as substitutes for dyes in the classical dye‐sensitized solar cells (DSCs). Here noble metal clusters protected by proteins and thiols (Au30 @BSA, Au25 SBB18, and Ag44 MBA30 ) have been used for photovoltaic studies. These metal clusters were used as sensitizers for the photoanodes fabricated using TiO2 nanotubes (NTs) and the commercial P25 TiO2 nanoparticles. The TiO2, clusters and the solar cells were characterized by spectroscopy, microscopy, current‐voltage ( I ‐ V ) and incident photon‐to‐current conversion efficiency (IPCE) measurements. A systematic I ‐ V study revealed a conversion efficiency of 0.35 % for the Au30 @BSA sensitized solar cell made from TiO2 NTs which showed an IPCE maximum of 3 % at ∼ 400 nm. Abstract : Noble metal clusters protected by proteins and thiols (Au30 @BSA, Au25 SBB18, and Ag44 MBA30 ) have been used for photovoltaic studies. These metal clusters were used as sensitizers for the photoanodes fabricated using TiO2 nanotubes (NTs) and the commercial P25 TiO2 nanoparticles. A systematic I ‐ V study revealed a conversion efficiency of 0.35 % for the Au30 @BSA‐sensitized solar cell made from TiO2 NTs.